The Role of the Audit Committee on Determinants Financial Distress with Zmijewski Model - Erik Hermawan; Nurmala Ahmar; M. Ardiansyah Syam (Budapest International Research and Critics University, 2022)
This study is a quantitative study that aims to determine, analyze, prove, and test the company's health status on the effect of Current Ratio, Debt to Equity Ratio, and Return on Assets on financial distress with the Audit Committee as a Moderating Variable. The analysis in this study uses the Zmijewski model. Where the Zmijewski (1984) model uses ratio analysis that measures the performance, leverage, and liquidity of a company for its prediction model. The data used in this study is secondary data originating from the annual reports of state-owned companies listed on the IDX (Indonesian Stock Exchange) for the 2014-2018 period. The results of this study indicate that the effect of the audit committee in moderating return on assets on financial distress is significant. Furthermore, the results of this study debt to equity ratio have a significant effect on financial distress. Meanwhile, the current ratio and return on assets have no significant effect on financial distress. The audit committee does not moderate the effect of the current ratio and debt to equity ratio on financial distress.